Correlates of HIV Status Nondisclosure by Pregnant Women Living With HIV to Their Male Partners in Uganda: A Cross-Sectional Study. (1st April 2021) - Bulterys, Michelle A.; Sharma, Monisha; Mugwanya, Kenneth; Stein, Gabrielle; Mujugira, Andrew; Nakyanzi, Agnes; Twohey-Jacobs, Lorraine; Ware, Norma C.; Heffron, Renee; Celum, Connie
Abstract : Background: HIV status disclosure by pregnant women living with HIV (PWLHIV) to their male partners is associated with improved maternal and infant outcomes. Understanding relationship factors associated with nondisclosure of HIV status by PWLHIV to their partners can inform the design of interventions to facilitate disclosure. Methods: We conducted a cross-sectional study using enrollment data from 500 PWLHIV unaware of their male partners' HIV status and participating in a randomized clinical trial assessing secondary distribution of HIV self-testing kits in Kampala, Uganda. The primary outcome was women's HIV status nondisclosure to their partners. We conducted univariate and multivariate binomial regressions to assess the association between baseline sociodemographic, HIV history, and relationship characteristics with HIV status nondisclosure. Results: 68.2% of the 500 PWLHIV had not disclosed their HIV status to their partner(s). Factors associated with higher likelihood of nondisclosure included relationship duration <1 year [adjusted prevalence ratio (aPR = 1.25); 95% confidence interval (CI): 1.02 to 1.54], being in a polygamous relationship (aPR = 1.21; 95% CI: 1.07 to 1.36), unmarried (aPR = 1.20; 95% CI: 1.07 to 1.35), uncertainty about whether their partner had ever tested for HIV (aPR = 1.55; 95% CI: 1.28 to 1.88), and a lack of social support from people aware of their status (aPR = 1.32; 95% CI: 1.18 to 1.49). Conclusion: Relationship factors, including shorter-term, unmarried, and polygamous relationships and uncertainty about partner's HIV testing history, were associated with higher likelihood of pregnant women's nondisclosure of HIV status to their partner. Interventions that facilitate couples' HIV testing and disclosure, provide counseling to reduce relationship dissolution in serodiscordant couples, and offer peer support for women may increase disclosure. ClinicaltrialsRegistration: Clinicaltrials.gov ID number: NCT03484533.